Robust Digital Data Hiding in Low Coefficient Region of Image (International Journal of Innovative Research in Computer Science & Technology, 2021)
Digital images have many uses in the field of  health, research, military, art, etc. Digital Images need  annotation for retrieval and protection from piracy, attacks, and modification. To perform this retrieval and protection, some of the information was hidden in the image matrix. This  paper proposes a data embedding and extraction algorithm.  Low-frequency regions of the image are identified to embed  secret information in LSV (Least Significant Value) and MSV (Most Significant Value) of a selected coefficient once the data hiding in the embedding section of the proposed model  image gets retransformed in the original image structure as per  the number of bits used in LSV and MSV for data hiding  image gets secured from different spatial attacks. The  experiment is performed on real images. A comparison of the  proposed model is done on PSNR, MSE, evaluation  parameters. It is shown that the proposed model is better as  compared to the existing model.
Keywords: Data Hiding; DIP; Information Embedding; Information Extraction; LSB; MSB